2000
DOI: 10.1562/0031-8655(2000)071<0730:apistc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence Patterns in Short-Term Cultures of Normal Cervical Tissue

Abstract: Fluorescence spectroscopy has potential to improve cervical precancer detection. The relationship between tissue biochemistry and fluorescence is poorly understood. The goal of this study was to characterize normal cervical autofluorescence, using fresh tissue short-term tissue cultures and epithelial cell suspensions. Transverse, short-term tissue cultures were prepared from 31 cervical biopsies; autofluorescence images were obtained at 380 and 460 nm excitation. Fluorescence excitation-emission matrices were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 17 publications
2
59
1
Order By: Relevance
“…The excitation±emission wavelength pairs of the tissue¯uorescence peaks were located at 300±345, 320±390, 340±460, and 460±520 nm, which are thought to correspond to tryptophan, collagen, NADH, and FAD, respectively [14]. The¯uorescence emission spectra of the frozen and thawed tissues at these excitation wavelengths are 30±50% of the corresponding in vivo state.…”
Section: Discussionmentioning
confidence: 94%
“…The excitation±emission wavelength pairs of the tissue¯uorescence peaks were located at 300±345, 320±390, 340±460, and 460±520 nm, which are thought to correspond to tryptophan, collagen, NADH, and FAD, respectively [14]. The¯uorescence emission spectra of the frozen and thawed tissues at these excitation wavelengths are 30±50% of the corresponding in vivo state.…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown that these whitening changes are valuable in reflectance measurements (9) and fluorescence measurements (10) in differentiation of neoplastic and normal cervical tissue. Data collected in this study from non-neoplastic cervical tissue reveal changes after the application of acetic acid (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Differences at 330 nm excitation can be attributed to changes in the¯uorescence of structural proteins, NADH, and reabsorption due to hemoglobin. The source of these changes can be explored using¯uorescence microscopy of short-term tissue cultures [14]. This pilot study suggests that such microscopy of normal and neoplastic ovarian tissue should be carried out at 330, 375, and 415 nm excitation.…”
Section: Discussionmentioning
confidence: 99%